R. Yehuda Al-Harizi's Translation of Taʾwil in Maimonides' Guide of the Perplexed: Philosophical Implications and Historical Impact on the Latin Translation - Tsadiḳ, Shalom (Jewish studies quarterly, 2023)
Because most readers of Maimonides' Guide of the Perplexed read it in translations, the exact understanding of these translations is very important for the history of the interpretation of the Guide. The aim of this article is to show that Al- Harizi's translations of the Judeo-Arabic word taʾwil have an important philosophical implication. His translations change a few critical passages in the Guide and make the radical (naturalist) interpretation of the Guide by the readers of this translation very improbable. By contrast, the translation by Samuel Ibn Tibbon makes this interpretation completely plausible (as does the Judeo-Arabic original). In my opinion the changes by Al-Harizi are part of his more traditional conservative interpretation of the Guide.